Potential Limitation for the use of Cyclosporine A as a Cardioprotective Agent during Donor Heart Retrieval and Storage. (July 2018) - Gao, Ling; Villanueva, Jeanette; Doyle, Aoife; Chew, Hong; Hicks, Mark; Jabbour, Andrew; Dhital, Kumud; Macdonald, Peter
Abstract : Background: The success of heart transplantation has allowed the consideration of older and sicker recipients for transplant but has necessitated consideration of hearts from "extended criteria" donors for transplant. We have successfully repurposed glyceryl trinitrate and erythropoietin for clinical use as additives to cardioplegic or protective cold flush solutions for routine clinical retrieval of marginal hearts from donors after both brain death or circulatory death (1, 2). Introduction of normothemic perfusion of the heart during transportation as an alternative to static cold storage has presented an opportunity to bolster the initial protective flush and the normothermic perfusate with extra cardioprotective agents. One such potential candidate is Cyclosporine A (CsA). It was shown to decrease cardiac ischemia reperfusion injury in pre-clinical models by minimizing mitochondrial permeability transition pore opening. The present study investigates the role of timing and duration of cardiac exposure to CsA during retrieval and storage on functional recovery and mechanisms of CsA action in a working rat heart model of donor heart preservation. Methods: After measurement of baseline function, hearts were arrested and stored for 6h at 4°C in either Celsior® alone or Celsior®+CsA (0.2μM), then reperfused for 45min in Krebs solution, when functional recovery was assessed. Two additional groups of Celsior®-alone stored hearts were exposed to 0.2μM CsA for the initial 15min (non-working period) or the full 45min period of reperfusion. Coronary effluent was collected pre- and post-storage for assessment of LDH release. Left ventricular free wall was snap-frozen after completion of each study for immunoblotting. Results: Presence of CsA during storage or the first 15min reperfusion significantly improved functional recovery and significantly increased phospho-AMPKThr172 and phospho-ULK-1Ser757. Hearts exposed to CsA for 45min post-reperfusion recovered poorly with no phospho-AMPK increase, decreased mitochondrial cyctochrome c content and increased LDH release. Conclusions: Inclusion of CsA at cardioplegia is cardioprotective. No extra benefit was gained by addition of CsA during the initial 15min reperfusion period. Presence of CsA for the full 45min reperfusion was toxic to the heart. Protective effects of CsA appear to be driven by activation of AMP associated protein kinase. References: 1. Kumarasinghe G et al. Int J Transplant Res Med 2016, 2:018. 2. Dhital KK, et al. Lancet 2015; 385: 2585-91. National Health & Medical Research Council (program grant ID 1074386), Australia. St Vincent's Clinical Foundation of Australia.